Soft-bubble grippers for robust and perceptive manipulation - Kuppuswamy, Naveen; Alspach, Alex; Uttamchandani, Avinash; Creasey, Sam; Ikeda, Takuya; Tedrake, Russ (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2020)
Manipulation in cluttered environments like homes requires stable grasps, precise placement and robustness against external contact. Towards addressing these challenges, we present the Soft-bubble gripper system that combines highly compliant gripping surfaces with dense-geometry visuotactile sensing and facilitates multiple kinds of tactile perception. We first present several mechanical design advances on the Soft-bubble sensors including a fabrication technique to deposit custom patterns to the internal surface of the sensor membrane that enables tracking of shear-induced displacement of the grasped object. The depth maps output by the internal imaging sensor are used in an in-hand proximity pose estimation framework - the method better captures distances to corners or edges on the object geometry. We also extend our previous work on tactile classification and integrate the system within a robust manipulation pipeline for cluttered home environments. The capabilities of the proposed system are demonstrated through robust execution of multiple real-world manipulation tasks.